1988
DOI: 10.1152/ajprenal.1988.254.6.f795
|View full text |Cite
|
Sign up to set email alerts
|

Proximal tubule Na+-K+-ATPase activity is inhibited during high-salt diet: evidence for DA-mediated effect

Abstract: Locally produced dopamine (DA) causes a reversible and dose-dependent inhibition in Na+-K+-ATPase activity in rat proximal tubule (PT) segments [A. Aperia, A. Bertorello, and I. Seri. Am. J. Physiol. 252 (Renal Fluid Electrolyte Physiol. 21): F32-F45, 1987.]. To examine whether this effect might be of physiological importance, rats were given normal-salt (NS) or high-salt (HS) diet for 10 days. HS diet significantly increased Na excretion but did not alter glomerular filtration rate (GFR). Benserazide (Bz), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
82
1
2

Year Published

1991
1991
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 0 publications
2
82
1
2
Order By: Relevance
“…The basal activity of Na ϩ ,K ϩ -ATPase was not different between rats on either NS or HS intake, and although this finding agrees with 1 report, 31 it differs from other published reports in which the authors found a decrease in basal Na ϩ ,K ϩ -ATPase activity in rats placed on an HS intake. 32 However, it should be noted that Bertorello et al 32 observed a decrease in basal Na ϩ ,K ϩ -ATPase activity in rats after 10 days of HS intake, whereas in the present study, we conducted our measurements after 24 hour of HS intake. It is likely that the exposure to HS intake needs to be of longer duration before changes in basal Na ϩ ,K ϩ -ATPase activity in rats can be observed.…”
Section: Discussionmentioning
confidence: 58%
“…The basal activity of Na ϩ ,K ϩ -ATPase was not different between rats on either NS or HS intake, and although this finding agrees with 1 report, 31 it differs from other published reports in which the authors found a decrease in basal Na ϩ ,K ϩ -ATPase activity in rats placed on an HS intake. 32 However, it should be noted that Bertorello et al 32 observed a decrease in basal Na ϩ ,K ϩ -ATPase activity in rats after 10 days of HS intake, whereas in the present study, we conducted our measurements after 24 hour of HS intake. It is likely that the exposure to HS intake needs to be of longer duration before changes in basal Na ϩ ,K ϩ -ATPase activity in rats can be observed.…”
Section: Discussionmentioning
confidence: 58%
“…The results presented here show that a substantial amount of newly-formed dopamine is deaminated to DOPAC; this occurs largely in the renal cortex where saturation of deamination of dopamine could be observed, but also to some extent in the medulla and this difference may be related to the limited production of dopamine in the rat renal medulla. Alternatively, it could be hypothesized that in the rat renal medulla the specific activity of MAO may exceed that in the renal cortex, as has been found to occur in the kidney of the cat (Caramona & Soares-daSilva, 1990 In recent years, several lines of evidence have suggested that dopamine may exert considerable effects within the kidney and contribute actively in the maintenance of blood pressure at levels considered as acceptable (Lee, 1982;Yoshimura & Takahashi, 1988;Bertorello et al, 1988). The activation of -I type D1 dopamine receptors in the renal vasculature produced vasodilatation resulting in increased renal blood flow and glomerular filtration rate (Felder et al, 1988).…”
Section: Discussionmentioning
confidence: 97%
“…Whereas the local actions of dopamine within proximal tubule cells have been described with some detail in the last few years, the factors that trigger the peripheral dopaminergic response still remained to be identified. A large increase in the content of sodium within the diet is directly related to the natriuretic response, and in vivo experiments have shown that dopamine does not inhibit proximal tubule sodium reabsorption unless there is a sodium load (33)(34)(35)(36). Because the dopaminergic response is initiated by synthesis of dopamine by the proximal tubule cells and the translocation of dopamine receptors from cytosolic storage compartments to the plasma membrane (37), there must be an intracellular mechanism that senses the presence of the sodium load.…”
Section: Discussionmentioning
confidence: 99%